Molecular collisions, photoionization and dynamics - Bettega, Márcio Henrique Franco (2022)
The topical issue “Advances on Molecular Collisions, Photoionization and Dynamics” encompasses a set of theoretical and experimental contributions honouring the unprecedented scientific career of our loyal colleague and trusted friend the late Professor Vincent McKoy. He has been a pioneer in implementing ab initio electron-molecule scattering and molecular photoionization theoretical methods, alongside with his collaborations across the globe, having contributed to different research fields that are now well-established and where he leaves a strong scientific legacy as noted by the testimony of his long-lasting collaborator, Carl Winstead. The contributions hereafter are related to the most recent achievements in electron interactions with molecules and molecular ions as a function of phase and stage of aggregation as well as key aspects of photoionization mechanisms therein. Particular topics include studies of photon and electron interactions (excitation, ionization and attachment) with biological, technological, astrophysical and aeronomic relevant molecules, electron transport phenomena and electron induced surface chemistry. Theoretical aspects of model potentials and molecular processes including nonadiabatic chemical reactions are also addressed in this special occasion.